2016
DOI: 10.1007/s00018-016-2138-9
|View full text |Cite
|
Sign up to set email alerts
|

Natural protein sequences are more intrinsically disordered than random sequences

Abstract: Most natural protein sequences have resulted from millions or even billions of years of evolution. How they differ from random sequences is not fully understood. Previous computational and experimental studies of random proteins generated from noncoding regions yielded inclusive results due to species-dependent codon biases and GC contents. Here, we approach this problem by investigating 10,000 sequences randomized at the amino acid level. Using well-established predictors for protein intrinsic disorder, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 46 publications
2
43
2
Order By: Relevance
“…8 Several studies had been conducted using randomly generated sequence and their findings suggest that random sequences have biological properties rather than previously thought inert sequence Neme et al 18 tested the hypothesis than random sequences can be considered inert and unlikely to give rise to functional genes. A library of DNA sequences averaging 700 bases was generated; of which, 150 bases were random sequences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Several studies had been conducted using randomly generated sequence and their findings suggest that random sequences have biological properties rather than previously thought inert sequence Neme et al 18 tested the hypothesis than random sequences can be considered inert and unlikely to give rise to functional genes. A library of DNA sequences averaging 700 bases was generated; of which, 150 bases were random sequences.…”
Section: Resultsmentioning
confidence: 99%
“…For example, 500 thousand randomly generated DNA sequences of 50 nucleotides each were used to examine the relationship between DNA sequences and gene expressions, 6 random peptide sequences had been used to study randomly arising secondary structures, 7 and natural peptides had been shown to have more longdisordered regions than randomly generated peptide sequences. 8 Several random sequence generators had been developed over the years. Many random nucleotide or amino acid generators provided minimal options; such as, fixed length and fixed GC content (http:// www.faculty.ucr.edu/~mmaduro/random.htm), random selection from a given sequence (http://www.dave-reed.com/Nifty/randSeq.…”
Section: Introductionmentioning
confidence: 99%
“…At first, we compared proteome-wide protein disorder content between real and random sequences in each of the 12 selected genomes. Comparing disorder content of few selected proteins mainly short peptides collected from UniRef databases with random sequences of same overall amino acid frequencies, Yu et al suggested that high protein disorder among natural sequences is a general evolutionary trend [23]. By contrast, in this systematic analysis, we compared the disorder content of real sequences of each species with their corresponding length conserved random sequences.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that previous speculation of high protein disorder among the naturally occurring protein sequences [23] is not a general trend among all organisms; instead, it is evident that prokaryotic and eukaryotic organisms show distinct trends.…”
Section: Introductionmentioning
confidence: 93%
“…Protein sequences are represented by a 20-symbol alphabet of amino acids. Since there is a high number of different amino acids in these sequences, with an intrinsically disordered nature, they are considered to be complex in terms of compression [12][13][14].…”
Section: Protein Sequence Compressionmentioning
confidence: 99%